Single Blind Randomized Controlled Trial of Modified Constraint-Induced Movement Therapy in Infants With the Sequelas of Unilateral Brachial Plexus Injury - Cui, Zhenzhen; Liu, Le; Chen, Xi; Zeng, Haiyan; Zheng, Shizhu; Wu, De (Frontiers in Human Neuroscience, 2022)
Objective To explore the effect of modified constraint-induced movement therapy (mCIMT) on upper limbs residual dysfunction for infancy with the sequelas of unilateral brachial plexus injury (uBPI). Methods Single blind randomized controlled trial of mCIMT vs. standard care. An enrolling 31 infants with a uBPI exhibiting residual dysfunction of the affected upper limb for over 6 months was conducted. And functional outcomes pertaining to the affected upper limb were assessed via AMS, GRES, RHS, and MSS at 0, 3, and 6 months after treatment. Results No differences were found in baseline (acquisition phase) AMS, MSS, GRES, or RHS between the control and mCIMT groups [F(1, 14) = 0.062, P = 0.086; F(1, 14) = 0.483, P = 0.499; F(1, 14) = 0.272, P = 0.610; Z = −0.336, P = 7.373]. At the 3- and 6-month follow-up time points, AMS, MSS, and GRES scores were significantly improved over baseline in both groups [mCIMT: F(2, 30) = 183.750, 128.614, 110.085, P < 0.05; Control: F(2, 28) = 204.007, 75.246, 51.070, P < 0.05]. No significant differences were found between two treatment groups at the 3-month follow-up time point [F(1, 14) = 0.565, P = 0.465; F(1, 14) = 0.228, P = 0.641; F(1, 14) = 0.713, P = 0.413; Z = −0.666, P = 0.505]. However, at the 6-month follow-up time point, AMS and MSS scores were significantly improved in the mCIMT group relative to the control group [F(1, 14) = 8.077, P = 0.013; F(1, 14) = 18.692, P = 0.001]. Conclusion mCIMT may benefit the rehabilitation of residual upper limb dysfunction associated with a uBPI in infants. Clinical Trial Registration [www.chictr.org.cn], identifier [ChiCTR1900022119].